Impact of the interplay between stemness features, p53 and pol iota on replication pathway choices. Issue 13 (24th June 2021) - Ihle, Michaela; Biber, Stephanie; Schroeder, Insa S; Blattner, Christine; Deniz, Miriam; Damia, Giovanna; Gottifredi, Vanesa; Wiesmüller, Lisa
Abstract: Using human embryonic, adult and cancer stem cells/stem cell-like cells (SCs), we demonstrate that DNA replication speed differs in SCs and their differentiated counterparts. While SCs decelerate DNA replication, differentiated cells synthesize DNA faster and accumulate DNA damage. Notably, both replication phenotypes depend on p53 and polymerase iota (POLι). By exploring protein interactions and newly synthesized DNA, we show that SCs promote complex formation of p53 and POLι at replication sites. Intriguingly, in SCs the translocase ZRANB3 is recruited to POLι and required for slow-down of DNA replication. The known role of ZRANB3 in fork reversal suggests that the p53–POLι complex mediates slow but safe bypass of replication barriers in SCs. In differentiated cells, POLι localizes more transiently to sites of DNA synthesis and no longer interacts with p53 facilitating fast POLι-dependent DNA replication. In this alternative scenario, POLι associates with the p53 target p21, which antagonizes PCNA poly-ubiquitination and, thereby potentially disfavors the recruitment of translocases. Altogether, we provide evidence for diametrically opposed DNA replication phenotypes in SCs and their differentiated counterparts putting DNA replication-based strategies in the spotlight for the creation of therapeutic opportunities targeting SCs.